Pengembangan Modul Digital Berbasis Flipbook Pada Pembelajaran IPA Materi Bumi dan Alam Semesta Untuk Siswa Kelas IV SD - Devi; Henni Riyanti; Patricia H.M.Lubis (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Muhammadiyah Sukabumi, 2024)
The purpose of this research is to develop flipbook-based digital modules for science learning on earth and the universe material for fourth grade elementary school students that are valid and practical and to find out the potential effects of using the fourth grade IPS SD digital module on student learning outcomes. The type of research used in this research is the Research and Development (R&D) method with the ADDIE development model. Questionnaire data collection techniques, tests, and documentation. Data analysis techniques were carried out to obtain flipbook-based digital modules according to the criteria of validity, practicality, and potential effects. After obtaining the data. The research results obtained flipbook-based digital modules which were stated to be very valid or feasible, the development of flipbook-based digital modules was declared valid, based on the results of the validity assessment according to media experts with an average score of 3.9 percentage 78.2%, linguists with an average score of an average of 4 percentages of 80% and material experts of getting an average score of 4.4 percentages of 86%. The development of a flipbook-based digital module was declared practical based on the results of the practicality assessment according to the student response questionnaire getting an average score of 4.7 with a percentage of 91.9%. The development of flipbook-based digital modules has a potential effect on students, based on the results of the evaluation of student evaluation results, a total average score of 8.5 is obtained with a percentage of 85%.